Implementation of Passive Leg Movement on Blood Pressure in Post-Op Laparatomy Exploration Patient - Setiyaningrum, Synthia Dwi; Ridla, Akhmad Zainur; Nistiandani, Ana; Gunarto, Sugito Tri (Al-Hijrah Indonesia, 2024)
Background: Management of secretions is one of the main problems faced in the medical condition of respiratory disorders. The use of complementary therapy techniques to treat airway clearance such as the active cycle of breathing technique is still low when compared with other interventions in treating respiratory problems. Aims: The research aims to determine the effectiveness of providing active cycle of breathing technique therapy to overcome nursing problems ineffectiveness airway clearance in nursing care. Method: This type of research is a case study using nursing care methods. The research sample was patients treated in the Catleya room at Dr. Soebandi Jember Hospital. Patients are given nursing intervention in the form of therapy active cycle of breathing technique for 4 consecutive days 2 times a day for 15-20 minutes with 4 cycles. Results: providing active cycle of breathing technique therapy can reduce nursing problems ineffectiveness airway clearance. Providing active cycle of breathing technique therapy effectively shows improvements in conditions such as improved respiratory frequency, reduced shortness of breath, and decreased sputum production. Conclusion: providing active cycle of breathing technique therapy effectively solve nursing problems ineffectiveness airway clearance.